A progressive consumption tax: an important instrument for stabilizing business cycles, or just an exotic idea? - Aleksandar Vasilev (Problems of Economic Transition, 2019)
We introduce progressive consumption taxation into a real-business-cycle setup augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of the presence of of progressive taxation of consumption expenditures for the stabilization of cyclical fluctuations in Bulgaria. We find the quantitative effect of such a tax to be very small, and thus not important for either business cycle stabilization, or public finance issues.
Keywords: E24; E32; 330; business cycles; progressive consumption taxation; Bulgaria